Objectively Measured Physical Activity Is Related to Cognitive Function in Older Adults. Issue 11 (November 2013) - Kerr, Jacqueline; Marshall, Simon J.; Patterson, Ruth E.; Marinac, Catherine R.; Natarajan, Loki; Rosenberg, Dori; Wasilenko, Kari; Crist, Katie
<x xml:space="preserve">Abstract</x> Objectives To explore the relationship between cognitive functioning and time spent at different intensities of physical activity (PA) in free‐living older adults. Design Cross sectional analyses. Setting Continuing care retirement communities. Participants Older adults residing in seven continuing care retirement communities in San Diego County with an average age of 83; 70% were female, and 35% had a graduate‐level education (N = 217). Measurements PA was measured objectively using hip worn accelerometers with data aggregated to the minute level. Three cut points were used to assess low light‐intensity PA (LLPA), high light‐intensity PA (HLPA), and moderate‐ to vigorous‐intensity PA (MVPA). The Trail Making Test (TMT) Parts A and B were completed, and time for each test (seconds) and time for Part B minus time for Part A (seconds) were used as measures of cognitive function. Variables were log‐transformed and entered into linear regression models adjusting for demographic factors (age, education, sex) and other PA intensity variables. Results LLPA was not related to any TMT test score. HLPA was significantly related to TMT A, B, and B minus A but only in unadjusted models. MVPA was related to TMT B and B minus A after adjusting for demographic variables. Conclusion There may be a dose response between PA intensity and cognitive functioning in older adults. The stronger findings supporting a relationship between MVPA and cognitive functioning are consistent with previous observational and intervention studies.